Quality management system in radiotherapy in the light of regulations applicable in Poland - Bogusz-Czerniewicz, Marta (Contemporary Oncology/Współczesna Onkologia, 2012)
The need to establish conditions for safe irradiation was noted in Poland back in 1986 in the Atomic Law, but for over 16 years no regulations regarding this aspect were passed. The radiological incident in Bialystok (Poland) in 2001 undeniably accelerated the implementation of new legal regulations. Nevertheless, in the absence of national guidelines until 2002, most health care institutions resorted to the quality management system (QMS) model proposed by the ISO norm 9001:2000. Eventually, practice proved the theory and the aforementioned model was also implemented into Polish acts of law defining basic requirements for QMS in radiotherapy. The aim of this work is to review current national regulations regarding QMS in radiotherapy, in particular those referring to standard procedures, the establishment of a commission for procedures and performance of external and internal clinical audits in oncological radiotherapy, as well as to present the process of their implementation into the practice of health care institutions.